Analisis Penentuan Harga Jual Cermin Alumunium Dengan Menggunakan Metode Cost-Plus Pricing Pada Toko Kaca Mulia Berkah Di Tenggarong - Anggareni, Aji Desilia (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2019)
Abstract: The purpose of this thesis research is to find out and examine the selling prices of aluminum mirrors that have been determined by the owner all this time and the calculation of selling prices in accordance with accounting rules by the results of the researchers calculation. The problem in this thesis are that the owner of Mulia Berkah Glass Store has not counting and categorized the cost components that shape the selling prices and have not set or targeted the expected profit from the selling prices that has been valid all this time. The conclusion are the selling prices of aluminum mirrors based on the calculation of researchers using the cost-plus pricing method with full costing approach and the variable costing approach for sizes 35 cm X 91 cm is Rp155.000,-, for sizes 45 cm X 91 cm is Rp172.000,-, for sizes 34 cm X 127 cm is Rp179.000,-, for sizes 35 cm X 127 cm is Rp181.000,-, and for sizes 48 cm X 127 cm is Rp205.000,-. With an expected profit is 1% of total assets with different mark-up percentages for each approach. The selling prices set by the owner has been lower compared to the selling prices calculated by researchers, this is because the owner of Mulia Berkah Glass Store only sets the selling prices based on market prices, where does not accounted and classified the cost components that shape the selling prices with overall and maximum, and have not set or targeted the expected profit from the selling prices. In outline, the selling prices set by the owner at this time is not the selling prices that profitable when compared to the selling prices a result of the researchers calculation. Keywords: Selling price, Cost-plus pricing